(Not) lost in foresight: Structuring futures complexity in a politically meaningful way - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2021)
From the perspective of policymakers, planning for the many uncertainties that the future brings is a complicated task. Because of the growing complexity of global affairs, more and more information is destined to land on the desks of decision makers. State-of-the-art futures analysis structures information about conceivable events and developments, thus supporting more effective and legitimate anticipatory governance. Forecasting and foresight, the dominant analytical approaches, serve different political functions. Forecasting geopolitical events is primarily relevant for the executive branch, which must act on short-term assessments. Foresight scenarios, on the other hand, significantly contribute to deliberations on the desirability of plausible mid- to long-term developments in consultative bodies such as parliaments. Both approaches should be utilized in EU policymaking.
Keywords: 320